RESPON MAHASISWA TERHADAP TAYANGAN DAKWAH ISLAMIYAH KHAZANAH (TRANS 7) DAN DAMAI INDONESIAKU (TV ONE) - Khoiruddin Muchtar; Faula Rahma Ghalia (IAIN Salatiga, 2018)
This study wanted to find out how the attention, acceptance, and understanding of journalistic students of the 2013 UIN Bandung class were on the shows of Islamic propaganda (TRANS7) and peace in Indonesia (TV One). Through survey methods with quantitative approaches that are partially analyzed, namely by Pearson product moment correlation analysis, coefficient of determination, and t test and analyzed by hypothesis testing. The results show that my attention to Indonesian peace shows is low, understanding of the response to treasure shows is 18% and the remaining 82% is determined by variables or other factors. As for the understanding of the response to my Indonesian peace shows by 0.1% and the remaining 99.9% determined by variables or other factors. The acceptance of journalistic students in the class of 2013 on the shows of the existence of a relationship between the response of students to the shows of treasures. Whereas for the 2013 journalistic student acceptance of Indonesian peace shows there is no significant relationship. AbstrakPenelitian ini ingin mengetahui bagaimana perhatian, penerimaan, dan pemahaman mahasiswa jurnalistik angkatan 2013 UIN Bandung terhadap tayangan dakwah islamiyah khazanah (TRANS7) dan damai Indonesiaku (TV One). Melalui metode survey dengan pendekatan kuantitatif yang dianalisis secara parsial yaitu dengan analisis korelasi pearson product moment, koefisien determinasi, dan uji t serta dianalisis secara uji hipotesis. Hasilnya menunjukan bahwa perhatian terhadap tayangan damai Indonesiaku rendah, pemahaman terhadap respon pada tayangan khazanah sebesar 18% dan sisanya 82% ditentukan oleh variabel atau faktor lain. Sedangkan untuk pemahaman terhadap respon pada tayangan damai Indonesiaku sebesar 0,1% dan sisanya 99,9% ditentukan oleh variabel atau faktor lain. Penerimaan mahasiswa jurnalistik angkatan 2013 terhadap tayangan khazanah adanya hubungan antara respon mahasiswa dengan tayangan khazanah . Sedangkan untuk penerimaan mahasiswa jurnalistik angkatan 2013 terhadap tayangan damai Indonesiaku tidak adanya hubungan yang signifikan.